Occult Breast Cancer Initially Presenting with Axillary Lymph Node Metastasis: A Case Report - Inyoung Youn; Mi-Ri Kwon (Journal of the Korean Society of Radiology)
Occult breast cancer presenting with axillary lymph node metastasis refers to carcinoma of unknown primary origin that is consistent with metastatic breast cancer initially presenting with axillary metastasis, without clinical or imaging evidence of a definitive primary breast tumor. The standardized treatment and prognosis of occult breast cancer remain unknown owing to its rarity. Herein, we report a case of a 59-year-old woman with occult breast cancer who presented with axillary metastasis. A comprehensive evaluation, including a thorough review of breast examination findings such as mammography and ultrasonography, breast MRI, lymph node biopsy with immunohistochemistry analysis, additional wholebody PET-CT, and testing for other tumor markers, can be crucial in diagnosing occult breast cancer. Therefore, effective communication among clinicians, radiologists, and pathologists throughout the diagnostic process, along with clear explanations to patients, is crucial for diagnosing this rare occult breast cancer.